KUCATA'KI: An Innovation of Population Administration Services in Makassar City - sulmiah Sulmiah; Andi Ria Islamiati; Herlina Sakawati; Widyawati Widyawati (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Kucata'ki is an innovation of death and birth population administration service in Makassar City. This paper aims to determine the application of Kucata'ki public service innovation in Makassar City and to find out the supporting and inhibiting factors in this application. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out by means of observation, interviews, and documentation. The data analysis technique uses condensation, data presentation, conclusion drawing and verification. The results of this study indicate that the implementation of Kucata'ki public service innovations in Makassar City has been going well. This can be seen from the three indicators that have been running well, namely: relative advantage, possibility of trial and ease of observation. Two other indicators that are still not good are: suitability and complexity. The supporting factors for the implementation of Kucata'ki public service innovations are the commitment of the Population and Civil Registry services to health facilities and urban villages as well as adequate human resources and infrastructure, while the inhibiting factor is in terms of technical constraints, namely the quality of the network.